Energy saving and efficient energy use by power electronic systems - Blaabjerg, F.; Wang, H.; Davari, P.; Qu, X.; Zare, Firuz (2017)
© Springer International Publishing AG 2017. In the development of the modern society, one of the key factors is to save energy in order to become more independent of other energy resources. Two important approaches can be taken—one is to change behavior and thereby save energy—the second one is to develop new technology which is able to save energy in different applications. This chapter will give an overview of challenges and possibilities in terms of energy saving and also energy efficient use. This includes a discussion on high efficiency power electronics devices and the systems they are used for energy loss reduction. The key enabling technologies are power electronics, Information and Communication Technology (ICT) as well as systems to carry the electrical energy through power transmission, conversion and distribution. A couple of examples will be given to demonstrate the energy saving possibilities by power electronics systems, such as in the applications of adjustable speed drives and solid-state lighting systems. Power electronics gives also a high flexibility when renewable power production is introduced to electrical energy systems. Future research opportunities and challenges will finally be discussed.